OC-030 Benefits of introduction of a symptom triggered regimen for management of alcohol withdrawal in a large teaching hospital trust: reduced admission duration and cost savings. (28th May 2012) - Lee, T J W; Samuel, M; Bewick, L; Rutherford, H; Perez, P; Gilvarry, E; Cunningham, M; Dipper, C; Masson, S
Abstract : Introduction: Acute alcohol withdrawal (AAW) is an increasingly frequent cause for hospital admission in the UK. NICE guidance (2010) recommends the use of a symptom triggered regimen (STR) rather than a fixed-dose regimen of benzodiazepines for the management of AAW. The aim of this study is to observe the effects of the introduction of a STR protocol as part of the introduction of a specialist Alcohol Liaison Team (ALT) in a large teaching hospital trust. Methods: Data were collected prospectively on all patients admitted for management of AAW during two 3-month periods; before and after the introduction of a symptom triggered regimen. The Clinical institute for Withdrawal Assessment for alcohol scale (CIWA-Ar) was used to assess AAW objectively. The introduction of the STR was overseen by an ALT consisting of a specialist nurse and a consultant at both hospital sites in the trust. Results: In the initial period, 102 patients were managed using a fixed-dose regime. Median length of stay (LoS) was 4.0 days (IQR 2–6 days). Median total chlordiazepoxide dose was 260 mg (IQR 120–490 mg). After introduction of STR, 119 patients were included. Median length of stay was 3.0 days (IQR 1.5-5.0 days). Median total chlordiazepoxide dose was 200 mg (IQR 55–450 mg). Age, gender and comorbidities in the before and after groups were comparable. The reduction in length of stay and total chlordiazepoxide dosage following introduction of the STR protocol were statistically significant (p<0.001). Conclusion: Introduction of a STR protocol for management of acute alcohol withdrawal was associated with a reduction in the length of stay and total benzodiazepine dose required. A specialist ALT facilitated the introduction of the STR at two hospital sites in a large teaching hospital trust. The reduction in length of stay alone could contribute to potential cost savings to the trust of around £280 000 per annum. This justifies the presence of an alcohol liaison team in the trust and supports the recommendations of the NICE guidelines. Competing interests: None declared.